Measuring Similarity between Groups of Trajectory Data with Multiple Aspects - Machado, Vanessa Lago; Portela, Tarlis Tortelli; Vanini, Lucas; Mello, Ronaldo dos Santos (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2024.242016, 2024)
This paper proposes an approach to measure similarity between groups of trajectory data using representative trajectories. By summarizing each group into a representative trajectory and comparing these, we address the challenges in group trajectory analysis. This offers a versatile solution for understanding group behaviors and interactions. Our approach is demonstrated using the Foursquare NYC dataset, which shows its potential in social behavior analysis and highlights its diverse applications, such as urban planning, transportation optimization, and animal migration analysis. The results show that our approach provides meaningful insights into group trajectory patterns, significantly advancing the field of trajectory data analysis.